(untitled) (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2014)
This work aims to study the impact of using Java Software of Geometrical Optics JSGO on the geometrical construction success of the virtual image among the pupils in the first year of Baccalaureate, option: Experimental Sciences (ES).To examine this impact, we realized an experiment towards the end of the school year 2012/2013 among a group of learner consisting of 43 pupils. These pupils took a pretest using the traditional method, followed by a formation on how to use JSGO and finally they set for a posttest using the mentioned software.The analysis of the results of our study â€œevolution of the nature of geometrical constructions producedâ€ confirms that using JSGO does not induce, in any case, the pupils to make an error in the construction of the virtual image.By analyzing the results concerning pupils conceptual difficultiesâ€ we have scored the presence of the conceptual difficulty associated with an incorrect status that about 32 % of learners attribute to the construction ray extension. The use of JSGO provides a useful tool to overcome this conceptual difficulty. This analysis also indicates that, despite the interactive character of JSGO, about 12 % of pupils still face the conceptual difficulty related to the correspondence image object (punctual and global) and also to the conceptual difficulty related to the minimum number of rays departing from the same point of the luminous object.Finally, the study of pupils perceptions about using JSGOâ€ showed that the participants are very satisfied with using this computer wizard.